Pre-oxidation effects on properties of bismuth telluride thermoelectric composites compacted by spark plasma sintering - Kim, Jinseo; Duy, Le Thai; Ahn, Byungmin; Seo, Hyungtak (Journal of Asian Ceramic Societies, 2020)
Research on harvesting alternative energy sources is of interest to meet human demands for energy while reducing environmental pollution caused by the extensive use of fossil fuels. Thermoelectric materials are a promising technology for converting heat into electricity. Among thermoelectric materials, the binary bismuth telluride system (Bi-Te) is widely used. To produce high-quality Bi-Te systems with low materials consumption, spark plasma sintering (SPS) is commonly applied. Because SPS is a fast low-temperature process, controlling the ratio and crystallization of Bi-Te is critical for effective energy conversion. Here, we investigated the quality of Bi-Te systems formed by SPS compaction of raw powders with an in-depth examination of the oxidation effects on their thermoelectric performance. With increasing measurement temperature (300→420 K), the mechanically mixed sample and a commercial Bi2Te3 alloy (sintered at 533 K) showed differences in Seebeck coefficients (0.245→0.267 and 0.223→0.246 mVK−1, respectively). The alloy sample showed a decreased figure of merit (0.863→0.331) while that of the mechanically mixed sample (0.543→1.671) increased with temperature. This was related to the degree of oxygen impurity in each Bi-Te process based on XPS analysis. This study proposes that the integration of oxygen species to Bi-Te can be considered to maximize the thermoelectric efficiency at the specified temperature.
Keywords: Alternative energy source; Bismuth telluride; Pre-oxidation; Thermo-Electric materials; thermoelectric; Thermoelectric efficiency; Thermoelectric performance; XPS analysis; Bismuth-telluride; pre-oxidation; spark plasma sintering; thermoelectric; XPS analysis